PENGARUH PENGEMBANGAN PENUNTUN DAN KIT PRAKTIKUM KIMIA TERINTEGRASI MODEL INKUIRI DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Akmalia, Nur; Silaban, Ramlan; Sari, Richa Purmaya (Lantanida Journal, 2025)
The aim of this study is to identify the validity of the practicum kit that has been developed, the validity of the chemistry practicum guide integrated with the inquiry model, and the impact of using chemistry practicum manuals and kits on student learning outcomes. This study was carried out to address a number of issues with the way chemistry practicum is implemented in schools, including a lack of resources and instruments, a procedural approach, and a low level of student participation. Participants in this study included practicum guides that were integrated with the Inquiry model, five chemistry teachers, two peer reviewers, two lecturers from Medan State University, and up to 22 MAS Muta'allimin Aceh Besar students in class XI MIA 1. According to the ADDIE framework, this experiment fits within the category of development research. Tests of student learning outcomes and validation sheets of practicum manuals and kits were used to gather data. SPSS 21 software was used to analyze the data using quantitative descriptive statistical techniques, such as normality tests and One Sample T-Test hypothesis testing. According to the results, the practicum kits and instructions created had an average score of 3.54, coming into the "very feasible" category. Furthermore, the average learning outcome for students using practicum kits and manuals is 3.54, coming into the "very feasible" category.